Fractional flow reserve versus angiography guided revascularization for patients with multivessel coronary artery disease: a systematic review and meta-analysis of randomized controlled trials. (3rd October 2022) - Goel, S; Slomovich, S; Edris, S; Park, W J; Agarwal, C; Hooda, A; Krishnamoorthy, P M; Gidwani, U; Sharma, S; Kini, A
Abstract: Background: Recently published randomized controlled trials (RCT) have questioned the utility of Fraction Flow Reserve (FFR) to guide revascularization in patients with multivessel coronary artery disease (CAD) as compared to Angiography Purpose: This current analysis aimed to compare the clinical outcomes associated with FFR guided versus standard angiography-guided revascularization for patients with multivessel CAD using a large number of randomized patients with stable CAD and acute coronary syndrome (ACS) Methods: We conducted an electronic database search of all published data for RCT that compared FFR versus Angiography for patients with multivessel CAD and reported on subsequent mortality, cardiac death, myocardial infarction, revascularization, and other outcomes of interest. Event rates were compared using a forest plot of odds ratios using a fixed-effects model assuming interstudy heterogeneity. Results: Eleven RCT (n=6052; FFR = 3043, Angiography = 3027) were included in the final analysis. Mean follow-up period was 1.7 years. In our analysis, FFR guided revascularization as compared to angiography guided revascularization alone was not associated with any significant reduction in overall mortality (OR = 1.10, 95% CI = 0.83–1.47, P=0.47, I 2 =0), cardiac mortality (OR = 0.95, 95% CI = 0.63–1.45, P=0.42, I 2 =0), all revascularization (OR = 0.96, 95% CI = 0.80–1.14, P=0.17, I 2 =31%) or myocardial infarction (OR = 0.99, 95% CI = 0.79–1.23, P=0.33, I 2 =12%). There was also no difference between two groups in terms of major adverse cardiac or cerebrovascular event [MACCE] (OR = 1.13, 95% CI = 0.90–1.42, P=0.39, I 2 =5%), major adverse cardiac event [MACE] (OR = 0.86, 95% CI = 0.70–1.07, P=0.55, I 2 =0), stroke/TIA (OR = 1.61, 95% CI = 0.92–2.82, P=0.36, I 2 =8%) or target lesion revascularization [TLR] (OR = 0.86, 95% CI = 0.44–1.67, P=0.71, I 2 =0). Furthermore, sensitivity analysis was conducted to include only studies with ACS patients and studies which used CABG only for revascularization. However, there was no difference between the two groups for any of the above outcomes Conclusion: There is no difference in clinical outcomes in patients undergoing FFR-guided versus angiography guided revascularization for multivessel CAD Funding Acknowledgement: Type of funding sources: None.